A nonlinear associations of metabolic score for insulin resistance index with incident diabetes: A retrospective Chinese cohort study - Chen, Zhuangsen; Huang, Caiyan; Zhou, Zhongyu; Zhang, Yanrong; Xu, Mingyan; Tang, Yingying; Fan, Lei; Feng, Kun (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background: The Metabolic score of insulin resistance (METS-IR) has recently been accepted as a reliable alternative to insulin resistance, which was demonstrated to be consistent with hyperinsulinemic-euglycemic clamp. Few researches have focused on the relationship between METS-IR and diabetes in Chinese. The purpose of this research was to explore the effect of METS-IR on new-onset diabetes in a large multicenter Chinese study. Methods: 116855 participators were included in the Chinese cohort study administered from 2010 to 2016. METS-IR was determined as Ln [(2*FPG) + TG]*BMI)/(Ln[HDL-C]). The participators were stratified by quartiles of METS-IR. To assess the effect of METS-IR on incident diabetes, the Cox regression model was constructed in this study. Stratification analysis and interaction tests were applied to detect the potential effect of METS-IR and incident diabetes among multiple subgroups. To verify whether there was a dose-response relationship between METS-IR and diabetes, a smooth curve fitting was performed. In addition, to further determine the performance of METS -IR in predicting incident diabetes, the receiver operating characteristic curve was conducted. Results: The average age of the research participators was 44.08 ± 12.93 years, and 62868 (53.8%) were men. METS-IR were linked with new-onset diabetes after adjusting for possible variables (Hazard ratio [HR]: 1.077; 95% confidence interval [CI]: 1.073-1.082, P < 0.0001), the onset risk for diabetes in Q4 group was 6.261-fold higher than those in Q1 group. Moreover, stratified analyses and interaction tests showed that interaction was detected in the subgroup of age, BMI, SBP, DBP, and FPG, there was no significant interaction between males and females. Furthermore, a dose-response correlation was detected between METS-IR and incident diabetes, the nonlinear relationship was revealed and the inflection point of METS-IR was calculated to be 44.43. When METS-IR≥44.43, compared with METS-IR < 44.43, the trend was gradually saturated, with log-likelihood ratio test P < 0.001. Additionally, the area under ROC of the METS-IR in predicting incident diabetes was 0.729, 0.718, and 0.720 at 3, 4, and 5 years, respectively. Conclusions: METS-IR was correlated with incident diabetes, and showed a nonlinear relationship. This study also found that METS-IR had good discrimination of diabetes.